Mechanism of Circadian Regulation in Ferroptosis of the BMAL1/NRF2 Pathway in Renal Ischemia–Reperfusion - Shang Xu; Qiao Tang; Haiyang Du; Jiatao Xie; Ruoxin He; Ruiyan Wang; Qian Sun (Biomedicines)
Background: Renal ischemia–reperfusion injury (IRI) is a frequent cause of kidney transplant failure. Recent studies have shown that the extent of injury is closely linked to ferroptosis, and the process of cellular ferroptosis is diurnal and regulated by circadian genes. NRF2, involved in iron–heme metabolism, may be related to ferroptosis. We hypothesize that the pathway plays a role in circadian regulation in ferroptosis in renal IRI. Methods: Using hematoxylin and eosin (H&E) staining, enzyme-linked immunosorbent assay (ELISA), Cell Counting Kit-8 (CCK8), flow cytometry, real-time quantitative reverse transcription PCR (qRT-PCR), and Western blotting, we analyzed renal tubular tissues in vivo and in vitro and compared the groups with IR injury treatment, inhibition of ferroptosis, and inhibition of BMAL1 gene expression at the ZT0 (zeitgeber time 0) and ZT12 (zeitgeber time 12) time points. Results: IR injury treatments caused exacerbation of injury, both in vivo and in vitro, and were more pronounced at the ZT12 time point, which correlates with circadian rhythms. The use of the ferroptosis inhibitor (Fer-I) attenuated IR injury, suggesting that IRI is associated with ferroptosis. In contrast, reduced BMAL1-gene expression exacerbated injury, and NRF2, which is elevated in IR injury, was suppressed. Conclusions: The circadian gene BMAL1 affects the circadian rhythm of ferroptosis in renal IRI through the regulation of NRF2 and its downstream pathway. In this study, renal injury is well ameliorated by the ferroptosis inhibitor, exhibiting potential as a therapeutic agent for use in renal transplantation.